Pengaruh Self Presentation terhadap Subjective Wellbeing pada Emerging Adulthood Pengguna Instagram di Kota Bandung - Muhammad Dandy Rizkiansyah; Siti Qodariah (Bandung Conference Series: Psychology Science, 2023)
Abstract. Self-presentation is an effort made by a person to present themself as someone who can be accepted by others. An asynchronous and editable social media space allows one to selectively self-present to benefit, form and maintain at least some lasting, positive, and significant interpersonal relationships. These underlie the desire for acceptance and belongingness in human behavior and illustrate that there is evidence to suggest a strong positive relationship to positive emotions and satisfaction with life that is an aspect of subjective wellbeing. The purpose of this study is to obtain empirical data on the effect of self-presentation on subjective wellbeing on emerging adulthood Instagram users. The measurement in this study for the self-presentation and subjective wellbeing is using the Self Presentation on Facebook Questionnaire (SPFBQ) by Michikyan et al, Satisfaction With Life Scale (SWLS) and Scale of Positive and Negative Experience (SPANE) by Diener, which have been modified and adapted. The criteria for the respondents to this study were Instagram users aged 18-24 years in the city of Bandung, there were 157 respondents. Based on the results of data analysis, it was found that there was a significant influence of self-presentation on subjective wellbeing of 16% on subjective wellbeing of cognitive aspects and an influence of 7% on subjective wellbeing of affective aspects. Keywords: Self Presentation, Subjective Wellbeing, Instagram, Emerging Adulthood Abstrak. Self presentation merupakan usaha yang dilakukan seseorang untuk menampilkan dirinya sebagai seseorang yang bisa diterima oleh orang lain. Ruang media sosial yang asynchronous dan editable memungkinkan seseorang melakukan self presentation secara selektif untuk memberikan keuntungan, membentuk dan mempertahankan setidaknya beberapa hubungan interpersonal yang langgeng, positif, dan signifikan. Hal-hal tersebut mendasari keinginan untuk acceptance dan belongingness pada perilaku manusia dan memberikan gambaran bahwa ada bukti yang menunjukkan hubungan positif yang kuat terhadap emosi positif dan kepuasan terhadap kehidupan yang menjadi aspek dari subjective wellbeing. Tujuan dari penelitian ini adalah memperoleh data empiris mengenai pengaruh self presentation terhadap subjective wellbeing pada emerging adulthood pengguna Instagram. Pengumpulan data dilakukan menggunakan Self Presentation on Facebook Questionnaire (SPFBQ) oleh Michikyan dkk, Satisfaction With Life Scale (SWLS) dan Scale of Positive and Negative Experience (SPANE) oleh Diener, yang telah dimodifikasi dan diadaptasi. Adapun kriteria dari responden penelitian ini adalah pengguna Instagram berusia 18-24 tahun di kota Bandung didapatkan berjumlah 157 responden. Berdasarkan hasil pengolahan data, didapati adanya pengaruh self presentation terhadap subjective wellbeing yang signifikan sebesar 16% terhadap subjective wellbeing aspek kognitif dan pengaruh sebesar 7% terhadap subjective wellbeing aspek afektif. Kata Kunci: Self Presentation, Subjective Wellbeing, Instagram, Emerging Adulthood.